2013
DOI: 10.1155/2013/797014
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Extreme Values by the Average Conditional Exceedance Rate Method

Abstract: This paper details a method for extreme value prediction on the basis of a sampled time series. The method is specifically designed to account for statistical dependence between the sampled data points in a precise manner. In fact, if properly used, the new method will provide statistical estimates of the exact extreme value distribution provided by the data in most cases of practical interest. It avoids the problem of having to decluster the data to ensure independence, which is a requisite component in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The univariate concept of average conditional exceedance rate (ACER) is a method for estimation of extreme wind speed statistics proposed by [80] and by [81] that have given an extension for estimation of extreme wind speed statistics to the case of bivariate wind speed time series based on the previous research on the Monte Carlo methods for estimating the extreme response of dynamic systems [82,83]. Naess and Karpa, 2015 [81] calibrated and tested the bivariate method for simultaneous wind speed measurements from two separate locations.…”
Section: Analytical Models Based On the Acer Approachmentioning
confidence: 99%
“…The univariate concept of average conditional exceedance rate (ACER) is a method for estimation of extreme wind speed statistics proposed by [80] and by [81] that have given an extension for estimation of extreme wind speed statistics to the case of bivariate wind speed time series based on the previous research on the Monte Carlo methods for estimating the extreme response of dynamic systems [82,83]. Naess and Karpa, 2015 [81] calibrated and tested the bivariate method for simultaneous wind speed measurements from two separate locations.…”
Section: Analytical Models Based On the Acer Approachmentioning
confidence: 99%
“…However, it has proven to be a suitable choice for the class of problems in this paper. In (Naess et al 2013) it is shown that the least squares optimization can be expressed as a weighted linear regression. Then the best choice of weight factor will be the inverse of the empirical variance for each value of (Montgomery et al 2001).…”
Section: Parametrizationmentioning
confidence: 99%
“…Naess et al suggested regression based on a generalized extreme value distribution, that is, εk()x=q1+a()xbcγ. …”
Section: Extreme Reliability Analysismentioning
confidence: 99%